Genotype x environment interaction and growth stability of exotic tree willow (Salix spp.) clones - Singh, N.B.; Sharma, J.P.; Choudhary, Punit; Gupta, R.K. (The Indian Journal of Genetics and Plant Breeding, 2017)
Eighteen selected clones of Salix were taken to study genotype x environment interaction. Significant differences were observed for genotype, environments and genotype x environment interaction except non-significant genotype x environment interaction for plant height increments. Stability analysis revealed that the most of the genotypes were responsive to environmental changes. TheSalix clones exhibited maximum growth in 2007 and 2010 growth years. Based on phenotypic indices (Pi), regression coefficient (bi) and deviation from regression (S2di) the clones J-799, SI-63-007 and NZ-1002 for volume index and SI-63-007 for diameter at breast height were found most adaptive to overall environments. Suitable clones for poor environment was J-194, while for average environments were V-99, NZ-1040 and NZ-1179, respectively for diameter at breast height. Clones suitable for rich environment are PN7-31 for diameter at breast height and NZ-1140 and 131/25 for volume index. The clones identified for different agro ecological regions must be chosen by considering stability of the clones towards that environment.